Social exchange approaches to promoting inter-organizational citizenship collaborative behaviors in the construction project team - Xue, Hong; Ling, Florence Yean Yng; Sun, Tao; Song, Yirou; Zheng, Junwei (Journal of Civil Engineering and Management, 2022)
Inter-organizational citizenship collaborative behavior (OCCB) is critical for project team members to share information and integrate resources. However, prior studies found that high OCCBs are absent in project teams. This study aims to explore social exchange approaches to promote project team members’ OCCBs in the construction project team from the social exchange perspective. A questionnaire survey was undertaken online. A two-stage SEM was conducted to verify the measurement and structural models. Confirmatory factor analysis was conducted to verify the measurement model’s reliability and validity, the structural model was assessed by examining the model’s fitness, and path coefficients were used to test the hypotheses. The findings showed that relational social exchange is more effective than contractual social exchange for OCCBs. Meanwhile, contractual control and benevolence trust are verified as mediators between competence trust and OCCB. Three pathways are explored to enhance project team members’ OCCBs: relational social exchange dominated strategy (i.e., dominant competence trust strategy and competence trust-benevolence trust strategy) and relational-contractual hybrid strategy (i.e., competence trust-contractual control strategy). This study expands the social exchange theory in the inter-organizational citizenship collaborative behavior in construction project teams and supports project management by verifying the enabling mechanisms.